Improving Children’s Fine Motor Skills Through Collage Activities At TK B Cahaya Qur’an Pagelaran Sub-District - Hasanah, Nida; Sulasiah, Siti; Umamah, Siti; Maulida, Alwanah; Halimatussaadiah, Siti; Alfiana, Fikri; Haerani, Elis (Jurnal Pendidikan Anak Usia Dini, 2026)
This research aims to improvethe fine motor skills of early childhood through fun and creative collage activities. Fine motor skills are skills thatinvolve the coordination of small muscles in the hands and fingers, which play an important rolein daily activities such as writing, drawing, and cutting.Collage activities are believed to be an effective means of developinghand-eye coordination and training children’s accuracy, patience, and independence.This study used a classroom action research (CAR) approach, whichwas carried out in two cycles with four stages, namely planning,implementation, observation, and reflection. The research subjects were 15 children in group Bat Cahaya Qur’an Kindergarten in Pagelaran Subdistrict, consisting of 15 children. Data were collected throughobservation, documentation, and interviews, then analyzed descriptivelyqualitatively to determine the improvement in children’s fine motor skills afterbeing given collage activities. The results showed thatcollage activities were able to significantly improve children’s fine motor skills. Children became more skilled in using tools such as scissorsand glue, more coordinated in moving their hands and fingers, andproduced neater and more creative work. In addition, this activityalso improved the children’s concentration, cooperation, and self-confidence during thelearning process. Thus, collage activities can be used as aneffective and enjoyable learning alternative in developingthe fine motor skills of early childhood in PAUD institutions.